Ménétrier's Disease as a Gastrointestinal Manifestation of Active Cytomegalovirus Infection in a 22-Month-Old Boy: A Case Report with a Review of the Literature of Korean Pediatric Cases - Jeana Hong; Seungkoo Lee; Yoonjung Shon (Korean Society of Gastrointestinal Endoscopy, 2018)
Ménétrier's disease (MD), which is characterized by hypertrophic gastric folds and foveolar cell hyperplasia, is the most common gastrointestinal (GI) cause of protein-losing enteropathy (PLE). The clinical course of MD in childhood differs from that in adults and has often been reported to be associated with cytomegalovirus (CMV) infection. We present a case of a previously healthy 22-month-old boy presenting with PLE, who was initially suspected to have an eosinophilic GI disorder. However, he was eventually confirmed, by detection of CMV DNA using polymerase chain reaction (PCR) with gastric tissue, to have MD associated with an active CMV infection. We suggest that endoscopic and pathological evaluation is necessary for the differential diagnosis of MD. In addition, CMV DNA detection using PCR analysis of biopsy tissue is recommended to confirm the etiologic agent of MD regardless of the patient's age or immune status.